A mesoscale subsurface eddy in the eastern Nansen Basin - Sholeninova, Polina (Helsingin yliopisto, 2021)
The Arctic Ocean is known to be inhabited with energetic mesoscale eddies commonly detected in depths from 200 m to 1200 m. Due to their high energetics and ability to transfer momentum, heat, salt and biochemical properties for long distances from their origin, eddies may considerably affect the structure of a water column in the Arctic Ocean. This study investigated an anticyclonic eddy event detected at one of the mooring stations deployed under the Nansen and Amundsen Basins Observational System project. The mooring located at the deep part of the continental slope of the Laptev Sea and conducted autonomous measurements during the years 2013–2015. The conductivity-temperature-depth, as well as current measurements from the Acoustic Doppler Current Profiler in the upper ocean (24–82 m) and from the McLane Moored Profiler in the intermediate layer (88–760 m), were examined. Spectral analysis of the currents and calculation of the eddy available potential energy were performed. This study revealed a mesoscale eddy with the core centred deeper than 750 m drifted past the mooring for 2 months. Its horizontal length scale was ∼128 km. The water properties typical for the Fram Strait Branch of the Atlantic water carried by the subsurface boundary current were trapped in the eddy. This study suggests that the eddy was originated from the baroclinic instability of the front between the Fram Strait Branch and the Barents Sea Branch of the Atlantic water flow.